Efficient nitrogen doping of graphene by plasma treatment. (January 2016) - Rybin, Maxim; Pereyaslavtsev, Alexander; Vasilieva, Tatiana; Myasnikov, Vladimir; Sokolov, Igor; Pavlova, Alexandra; Obraztsova, Ekaterina; Khomich, Andrey; Ralchenko, Viktor; Obraztsova, Elena
Abstract: Doping of pristine materials can change their chemical and electrical properties. Namely nitrogen doping of graphene results in modulation of electronic properties of graphene. In this work we present experimental results on nitrogen doped graphene fabricated in two steps. At first, the graphene samples were synthesized by a chemical vapor deposition method on copper foils. Then they were treated with ammonia radio frequency discharge plasma. The prepared samples were investigated by atomic-force microscopy (AFM), scanning electron microscopy (SEM), Raman spectroscopy, optical absorption spectroscopy including Fourier transform infrared spectroscopy (FTIR), X-ray and ultraviolet photoelectron spectroscopy. In doped graphene a dependence of N-atom concentration on the treatment parameters has been revealed. A maximum doping level of 3 atomic % has been obtained and the shift of valence band maximum of 0.2 eV was observed at this concentration of nitrogen.